Barging and Transshipment Market Research in the Coal Logistics Industry in Indonesia - Yusniar, Meina Wulansari; Ary Helmina, Monica Rahardian; Rifani, Ahmad (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This market research aims to analyze opportunities for coal barging and transshipment companies in Indonesia, analyze the market prices for transport barging & transhipment in 2023 and 2024, identify factors that affect the performance of coal logistics companies in Indonesian as well as prospects and strategies implemented by the coal Logistics industry. This type of research is qualitative research. The method of qualitative research is done using a survey method that describes, explains and interprets a phenomenon that occurs in an object and data is qualitatively characterized. The research was conducted qualitatively through interviews with companies operating in the field of coal logistics and coal users’ logistics. The results of the research conclude that the coal logistics industry in the future still has a fairly high prospect of business. As the largest island country with the longest coastline in the world, Indonesia has the potential and advantages to be optimized as a strategic maritime transport route. With coal reserves awakened, then coal production in Indonesia is also expected to increase with the national production target of 2024 to 922.14 million tons. This growth of production will improve the performance of the coal transportation sector, thus creating a positive business prospect for the coal logistics industry